Exploring teachers' perceptions of learner-aggressive behaviours in primary school at the Pinetown district in South Africa - Patrick Mweli; Emily Perumal (International Journal of Studies in Psychology)
Aggressive behaviour can be categorised into different forms, including physical violence, verbal aggression, and disruptive conduct. This study explores teachers' perceptions of learner-aggressive behaviour in inclusive school settings. It employed a qualitative approach, which used interpretive paradigm within the phenomenological design. It used semi-interviews and collages to gather data. The data analysis was done by utilising the thematic analyses technique to arrive at the overall findings. The study revealed that teachers perceive frustration as the leading cause of learner-aggressive behaviours within the classroom. The latter statement implies that learner-aggressive behaviours disrupt the learning environment and result in low learner academic achievement and teacher stress and burnout.